Utopia, Archive, and Anarchy in Los siete hijos de Simenon by Ramón Díaz Eterovic - Lila McDowell Carlsen (Studies in 20th & 21st Century Literature, 2011)
The detective narratives by Ramón Díaz Eterovic (Chile 1956) address some of Latin America’s most relevant socio-political problems, such as the disappeared, racial discrimination, drug trafficking, corruption, social oppression, and ecological negligence. While some critics have emphasized specific social issues of the new detective novel and, in particular, the novel by Díaz Eterovic studied here, Los siete hijos de Simenon (2000) ‘The Seven Sons of Simenon,’ less attention has been placed on the ideological and ethical foundation from which these social issues emerge. This novel displays a utopian perspective that points directly to a distorted system of values evident during the current post-dictatorial period in Chile. The central ideological motivation of Los siete hijos de Simenon proposes a renewed utopian impulse by means of anarchism and archiving. Finally, this essay proposes that Díaz Eterovic’s anarchist-utopian vision relates to the novel’s incorporation of literary allusions and references to anarchist figures, forming an archive of individual resistance that empowers the protagonist Heredia’s stance against official discourses.
Keywords: Los siete hijos de Simenon; Ramón Díaz Eterovic; detective narrative; Chilean literature; socio-political; ideology; utopian; post-dictatorial period; anarchism